Implications of the United States Medical Licensing Examination Step 1 Examination Transition to Pass/Fail on Medical Students Education and Future Career Opportunities. Issue 8 (August 2021) - Ehrlich, Haley; Sutherland, Mason; McKenney, Mark; Elkbuli, Adel
Background: United States Medical Licensing Examination (USMLE) Step 1 will transition to pass/fail score by 2022. We aim to investigate US medical students' perspectives on the potential implications this transition would have on their education and career opportunities. Methods: A cross-sectional study investigating US medical students' perspectives on the implications of transition of the USMLE Step 1 exam to pass/fail. Students were asked their preferences regarding various aspects of the USMLE Step 1 examination, including activities, educational opportunities, expenses regarding preparation for the examination, and future career opportunities. Results: 215 medical students responded to the survey, 59.1% were women, 80.9% were allopathic vs. 19.1% osteopathic students. 34.0% preferred the USMLE Step 1 to be graded on a pass/fail score, whereas 53.5% preferred a numeric scale. Osteopathic vs. allopathic students were more likely to report that the pass/fail transition will negatively impact their residency match (aOR = 1.454, 95% CI: 0.515, 4.106) and specialty of choice (aOR = 3.187, 95% CI: 0.980, 10.359). 57.7% of respondents reported that the transition to a pass/fail grading system will change their study habits. Conclusions: The transition of the USMLE Step 1 to a pass/fail system has massive implications on medical students and residency programs alike. Though the majority of medical students did not prefer the USMLE Step 1 to have a pass/fail score, they must adapt their strategies to remain competitive for residency applications. Residency programs should create a composite score based off all aspects of medical students' applications in order to create a holistic and fair evaluation and ranking system.